All Days 2006
DOI: 10.2118/98891-ms
|View full text |Cite
|
Sign up to set email alerts
|

Cementing of an Offshore Disposal Well Using a Novel Sealant That Withstands Pressure and Temperature Cycles

Abstract: A dedicated injector well, located in the Grane field in the Norwegian North Sea, was chosen as a candidate for application of a novel new sealant. The injector well, drilled for disposal of cuttings and produced water, was selected because of expected temperature and pressure cycling during the injection operation, and the risk of cement sheath integrity failure. This paper will discuss the design, execution, and evaluation of this injector well. Stress modeling indicated that as wellbore te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The UCS of the samples was measured on 50-mm-long by 25-mm-diameter cylindrical samples using the equipment described by Pedersen et al 7 The loading rate was 17.9 kN/min.…”
Section: Properties Of Resulting Permeable Cementmentioning
confidence: 99%
“…The UCS of the samples was measured on 50-mm-long by 25-mm-diameter cylindrical samples using the equipment described by Pedersen et al 7 The loading rate was 17.9 kN/min.…”
Section: Properties Of Resulting Permeable Cementmentioning
confidence: 99%
“…Compressive strength is one of the key characteristics that have a great influence on wellbore integrity at higher pressure conditions to ensure the structural support for the casing and hydraulic/mechanical isolation in the downhole environment (Di Lullo & Rae, 2000). Investigations on class G cement have concluded that conventional OPC is not capable of bearing the stress created by frequent pressure and temperature changes in wellbores (Pedersen et al, 2006). Researchers have experienced that the performance of OPC-based wells dropped after 15 years when the wells were exposed to 180 ºC and 22% CO2, and it was noticed that CO2 is the main reason for degradation.…”
Section: Compressive Strength and Tensile Strength Of Fa-based Geopol...mentioning
confidence: 99%